HAGIOGRAPHICA - Nock, A. D. (The journal of theological studies, 1927)
A. D. NOCK; HAGIOGRAPHICA, The Journal of Theological Studies, Volume os-XXVIII, Issue July, 1 July 1927, Pages 409–417, https://doi.org/10.1093/jts/os-XXVIII.J